PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP IPAS SISWA KELAS IV SD INPRES 5/81 BAJOE KABUPATEN BONE - Sudarto Sudarto; Sitti Rahmi; Lia Saputri (STKIP Subang, 2026)
This study is a pre-experimental study with a One Group Pretest-Posttest design. The aim of this reseach is determining whether the use of the PBL learning model influences or not the understanding of science concepts of students at SD Inpres 5/81 Bajoe, Bone Regency. The population in this study was all of 16 fourth-grade students. This study used a saturated sampling technique. Data collection techniques used tests. Data analysis techniques used were descriptive statistics and inferential statistics. The results showed that an average pretest score of 53.43 and posttest score of 72.50; t count (1.94) > t table (2.13). Conclusion: The use of the PBL learning model influences the understanding of science concepts of fourth-grade students at SD Inpres 5/81 Bajoe, Bone Regency.